Associação entre polimorfismos nos genes IL 10, IL 4, CTLA4 E Diamino oxidase e hipersensibilidade não alérgica a anti-inflamatórios não esteroidais - Vasconcelos, Luciana Mabel Ferreira (2017)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are responsible for 20to 25% of the adverse drug reactions. In susceptible individuals, itcan occurNSAIDs-exacerbated respiratory disease, NSAIDs-exacerbated cutaneous disease, NSAIDs-induced angioedema/urticaria and angioedema/ hives or anaphylaxisinduced to a single NSAID. The mechanisms of these reactions are not totally known, but there is high evidence that one of them is related to the inhibition of cyclooxygenase-1, what can lead to an overproduction of leukotrienes. It is possible that single nucleotide polymorphisms (SNPs) in genes associated with the inflammatory response promote a greater susceptibility to NSAIDshypersensitivity. The influence of genetic factors in modifying the individual's response to drugs, including NSAIDs, has become a promising challenge in the field of pharmacogenetics.The objective of the present study was to evaluate genetic polymorphisms of molecules involved in cross-sensitivity to NSAIDs.Interleukin-4 (-589 C/T, rs2243250), interleukin-10 (-1082 G/A, rs1800896), diamino oxidase (+8956C/G, rs 1049793), CTLA-4 (+49A/Grs231775)polymorphismswere investigated. Usingthe polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique, DNA samples extracted from peripheral blood of patients and controls were analyzed. On 14 March 2014,the study was approved by the Research Ethics Comitee at Hospital Universitário Walter Cantídio, number 550.608.Regardingthe IL10-1082 polymorphism, higher frequencies of the AG genotype (57.4%) (p = 0.018) and G allele carriers were found among the patients (70.4%) (p = 0.010) than among controls (38.9% and 48.4%, respectively).The G allele was found to be significantly associated with NSAIDS hypersensitivity (p = 0.025). For CTLA4 +49 A/G SNP, AG genotype (30.9%) (p = 0.012) and A carrier (52.7%) (p = 0.033) frequencies were found to be significantly lower in the patient group when compared with the control group (52.1% versus 71.3%). A significant association was also found between IL10-1082AG and IL4-589CC in NSAIDS hypersensitivity patients (p = 0.031),which indicated that individuals bearing those genotypes concurrently presented about 3.5 times probability of having NSAID crossreactive hypersensitivity. These findings suggest that individuals who have intermediate IL-10 levels, lowerCTLA-4 expression, and low IL-4 levels are more proneto present with cross reactive hypersensitivity.This is the first Brazilian study to carry out the association between polymorphisms in cytokine, CTLA-4 and DAO genes in a clinically well-characterized population of patients with NSAID cross-hypersensitivity. The prospect that, in the near future, these reactions are avoided in the population was the main motive that drove the realization of this work. For this to be a reality, it is necessary to deepen the study oftheinfluence of genetic and environmental factors on the modification of the individual's response to these drugs.